10.61533 PENERAPAN GREEN ACCOUNTING UNTUK MENILAI DAMPAK EKOLOGIS PENGGUNAAN ALAT MEDIS HABIS PAKAI DISEKTOR KESEHATAN PADA RUMAH SAKIT BAKTI TIMAH - Caecilia Octalica; Hendarti Tri Setyo Mulyani; Zamhari (STIE IBEK Pangkalpinang, 2026)
This study aims to analyze the application of green accounting in assessing the ecological impact of the use of consumable medical devices in the health sector at Bakti Timah Hospital. The technique for data collection uses interview, observation, and documentation techniques in the Environmental Health section of Bakti Timah Hospital using Descriptive Qualitative research methods. The results of this study indicate that Bakti Timah Hospital has actually implemented green accounting to assess ecological impacts, because it has recorded environmental impact costs, carried out various ways to prevent environmental impacts around the hospital and carried out effective waste management of consumable medical devices, it's just that the recording of environmental impact costs is still not specifically categorized and is still recorded in the financial section of general operating costs only.